Blood markers of neuronal/axonal and glial injury for clinical progression in a predominately Hispanic cohort: The Texas Alzheimer's Research and Care Consortium. (31st December 2021) - Gonzales, Mitzi M.; Wang, Chen‐Pin; Short, Meghan I.; MacCarthy, Daniel; Kautz, Tiffany; Satizabal, Claudia L.; Zare, Habil; O'Bryant, Sid; Seshadri, Sudha
Abstract: Background: The clinical translation of biofluid markers for Alzheimer's disease and related dementias (ADRDs) requires validation in diverse cohorts. The goal of the study was to evaluate if blood biomarkers of neuronal/axonal and glial injury predict cognitive decline and clinical disease progression in a predominately Hispanic cohort from the Texas Alzheimer's Research and Care Consortium. Method: Participants included 745 Hispanic and 274 non‐Hispanic white participants, aged 55‐89 years, who annually completed cognitive assessments, the Clinical Dementia Rating scale (CDR), and dementia consensus reviews. Serum from the baseline examination was assayed to quantify levels of total tau (t‐tau), neurofilament light (NFL), ubiquitin carboxyl‐terminal hydrolase LI (UCHLI), and glial fibrillary acidic protein (GFAP) using the Simoa Neurology 4‐Plex Kit (Quanterix), as well as soluble CD14 (sCD14) and chitinase‐3‐like protein 1 (YKL‐40) using commercial ELISAs (R&D Systems). Generalized estimating equations were used to evaluate the associations between serum biomarkers and longitudinal cognitive outcomes, as well as disease progression (CDR Sum of Boxes), adjusting for covariates of age, sex, ethnicity, education, body mass index, systolic blood pressure, diabetes, APOE ε4 status, and clinical diagnosis. Cox proportional hazard models were used to evaluate the associations between serum biomarkers and incident mild cognitive impairment (MCI) and dementia with adjustment for the covariates listed above. Result: Across the average four‐year follow‐up period, 162 individuals developed MCI and 96 developed dementia (Table 1). As displayed in Table 2, serum GFAP levels predicted cognitive decline across most cognitive domains. Serum t‐tau levels were associated with declines in global cognition, learning, and memory. Serum GFAP (b=0.154, SE=0.028, p<0.001), NFL (b=0.069, SE=0.026, p=0.007), and t‐tau (b=0.065, SE=0.023, p=0.004) predicted clinical progression. Higher GFAP levels at baseline were associated with increased risk of incident dementia (HR=1.485, p=0.009). None of the biomarkers predicted incident MCI. Conclusion: Serum GFAP levels were associated with multi‐domain cognitive decline, clinical progression, and incident dementia risk. The results suggest that reactive astrogliosis may be an important mechanism underlying a progressive neurodegenerative disease course in our predominately Hispanic sample. With further validation, serum GFAP may hold utility for predicting disease progression and monitoring the efficacy of newly emerging treatments.